2015
DOI: 10.1001/jamadermatol.2014.2211
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Keratosis Pilaris With 810-nm Diode Laser

Abstract: clinicaltrials.gov Identifier: NCT01281644.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The 532‐nm potassium titanyl phosphate laser (KTPL) has shown efficacy in one case report without the PDL‐associated bruise‐like discoloration after treatment . A randomized control study reported that the 810‐nm long‐pulsed diode laser was effective in treating KP . Combination modalities as PDL combined with long‐pulsed 755‐nm alexandrite laser and microdermabrasion have also shown some efficacy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 532‐nm potassium titanyl phosphate laser (KTPL) has shown efficacy in one case report without the PDL‐associated bruise‐like discoloration after treatment . A randomized control study reported that the 810‐nm long‐pulsed diode laser was effective in treating KP . Combination modalities as PDL combined with long‐pulsed 755‐nm alexandrite laser and microdermabrasion have also shown some efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modalities have been tried with variable success including, emollients, exfoliants, and anti‐inflammatory agents, such as urea, salicylic acid, lactic acid, topical corticosteroids, topical retinoids, and cholecalciferol . Phototherapy and various lasers such as the 532‐, 585‐, and 595‐nm vascular devices have also been used with some improvement, especially reducing redness.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of PDL is thought to be attributable to the induced apoptosis of vascular endothelial cells, and it may also lower vascular endothelial growth factor levels . A recent study by Ibrahim et al suggested that the 810‐nm diode laser was an effective treatment for improving skin texture in keratosis pilaris, but they reported no improvement in baseline erythema.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement in skin texture and roughness/bumpiness was noted in KP patients after 3 treatment visits spaced 4–5 weeks apart with the 810-nm diode laser. [ 54 ]…”
Section: U Nconventional I Ndications Ofmentioning
confidence: 99%